Strategies for the Internationalization of SMEs in Indonesia: The Role of Networks, Diasporas, and Business Associations - Agus Kurniadi; Sudarmiatin Sudarmiatin; Heri Pratikto (Harmoni Economics: International Journal of Economics and Accounting, 2026)
The internationalization of SMEs is a key strategy to enhance competitiveness and access global markets. However, many Indonesian SMEs face challenges such as limited information, networks, export capacity, and understanding of international markets. This study analyzes SME internationalization strategies in Indonesia by examining the roles of global networks, diaspora, and business associations as key supporting factors. Using a qualitative case study approach, data were collected through interviews, observations, and documentation of SME actors, diaspora members, and business association representatives. Thematic analysis was conducted through data reduction, presentation, and inductive conclusions. Findings show that global networks facilitate market access, provide international business information, and strengthen cross-border collaboration opportunities. The diaspora serves as a bridge market to promote products, build trust, and expand distribution. Business associations enhance SME readiness through training, export support, and global buyer access. Synergy among networks, diaspora, and associations creates a more effective collaborative ecosystem than individual approaches. Challenges such as low digital literacy, complex regulations, and capacity constraints remain. The study contributes theoretically by integrating these roles into SME internationalization literature and offers practical implications for SMEs and policymakers to strengthen a collaborative, network-based internationalization ecosystem.